Ponds & Water Features - Robinson, Peter (London Dorling Kindersley, 1999)
A guide providing practical information on the building and cultivation of ponds. This book is one of a series that addresses specific plants or plant groups, garden problems, design and planning solutions, as well as building projects for garden structures and features.
Include Color Illustration and Index
Keywords: Water gardens -- Water in landscape architecture